Procedural and post-operative complications associated with laparoscopic versus open abdominal surgery for right-sided colonic cancer resection: A systematic review and meta-analysis. Issue 40 (2nd October 2020) - Li, Yong Sheng; Meng, Fan Chun; Lin, Jun Kai
Abstract: Background: In this analysis, we aimed to systematically compare the procedural and post-operative complications (POC) associated with laparoscopic versus open abdominal surgery for right-sided colonic cancer resection. Methods: We searched MEDLINE, http://www.ClinicalTrials.gov, EMBASE, Web of Science, Cochrane Central, and Google scholar for English studies comparing the POC in patients who underwent laparoscopic versus open surgery (OS) for right colonic cancer. Data were assessed by the Cochrane-based RevMan 5.4 software (The Cochrane Community, London, UK). Mean difference (MD) with 95% confidence intervals (CIs) were used to represent the results for continuous variables, whereas risk ratios (RR) with 95% CIs were used for dichotomous data. Results: Twenty-six studies involving a total number of 3410 participants with right colonic carcinoma were included in this analysis. One thousand five hundred and fifteen participants were assigned to undergo invasive laparoscopic surgery whereas 1895 participants were assigned to the open abdominal surgery. Our results showed that the open resection was associated with a shorter length of surgery (MD: 48.63, 95% CI: 30.15–67.12; P  = .00001) whereas laparoscopic intervention was associated with a shorter hospital stay [MD (–3.09), 95% CI [–5.82 to (–0.37)]; P  = .03]. In addition, POC such as anastomotic leak (RR: 0.96, 95% CI: 0.60–1.55; P  = .88), abdominal abscess (RR: 1.13, 95% CI: 0.52–2.49; P  = .75), pulmonary embolism (RR: 0.40, 95% CI: 0.09–1.69; P  = .21) and deep vein thrombosis (RR: 0.94, 95% CI: 0.39–2.28; P  = .89) were not significantly different. Paralytic ileus (RR: 0.87, 95% CI: 0.67–1.11; P  = .26), intra-abdominal infection (RR: 0.82, 95% CI: 0.15–4.48; P  = .82), pulmonary complications (RR: 0.83, 95% CI: 0.57–1.20; P  = .32), cardiac complications (RR: 0.73, 95% CI: 0.42–1.27; P  = .27) and urological complications (RR: 0.83, 95% CI: 0.52–1.33; P  = .44) were also similarly manifested. Our analysis also showed 30-day re-admission and re-operation, and mortality to be similar between laparoscopic versus OS for right colonic carcinoma resection. However, surgical wound infection (RR: 0.65, 95% CI: 0.50–0.86; P  = .002) was significantly higher with the OS. Conclusions: In conclusion, laparoscopic surgery was almost comparable to OS in terms of post-operative outcomes for right-sided colonic cancer resection and was not associated with higher unwanted outcomes. Therefore, laparoscopic intervention should be considered as safe as the open abdominal surgery for right-sided colonic cancer resection, with a decreased hospital stay.